MCM-41 as a new separator material for electrochemical cell: application in zinc–air system - Saputra, Hens; Othman, Raihan; Sutjipto, Agus Geter Edy; Muhida, Riza (ELSEVIER, 2011)
The efficacy of nanoporous inorganic MCM-41 membrane as a new separator material for electrochemical cell has been investigated. The hexagonally ordered, narrow pore structure of MCM-41 membrane serves as ion exchange channels between the anolyte and catholyte of an electrochemical cell. Besides, it also acts as the electrolyte matrix or reservoir due to the hydrophilic nature of the as-synthesized MCM-41 and along with the high surface area and pore volume density characteristics. MCM-41 membrane has been employed as separator in zinc–air electrochemical system. MCM-41 was synthesized on the zinc substrate by dip-coating method and its thickness was ca. 5 micron. The Zn/MCM-41/air cell was able to produce a maximum power density of 32 mW/cm2 and possessed a volumetric energy density of 300 Wh/l, which are considered comparable to the published product datasheet of commercial zinc–air button cells of equivalent size.